Karakteristik Fisik Bubuk Jus Jambu Biji Merah (Psidium Guajava L.) yang Dikeringkan dengan Metode Foam-Mat Drying - Kintan Sari Kinanti; Syarifa Ramadhani Nurbaya; Rima Azara (PHARMADEMICA : Jurnal Kefarmasian dan Gizi, 2023)
Red guava is a type of fruit that has a relatively complete nutritional content, especially high in vitamin A. However, due to its high water content, red guava is susceptible to damage and cannot be stored for a long period. Drying is one of the methods that can extend the shelf life of fruits. This study aims to determine the effect of adding maltodextrin and egg white concentrations with or without blanching on the characteristics of red guava juice powder. From the physical analysis, blanching, and the addition of maltodextrin and egg white concentrations affect the solubility and color of red guava juice powder. The highest solubility percentage was obtained by adding 15% maltodextrin concentration and 6% egg white concentration with blanching (43.45%). The brightest and reddest color of the red guava juice powder was obtained by blanching treatment, while the bulk density of the red guava juice powder had the same value for blanching and non-blanching treatments, between 0.50 g/mL - 0.67 g/mL.